The Implementation of Connecting People in Community Mental Health Teams in England: A Quasi-Experimental Study. (29th September 2020) - Webber, M; Ngamaba, K; Moran, N; Pinfold, V; Boehnke, J R; Knapp, M; Henderson, C; Rehill, A; Morris, D
Abstract: Loneliness and social isolation have become significant concerns in many countries, particularly amongst people experiencing mental health problems. A social intervention—Connecting People—has been found to increase their access to social capital, though it has been difficult to implement with high fidelity in community mental health teams (CMHTs) in England. This study aimed to evaluate outcomes for mental health service users of a practitioner-led implementation of Connecting People in CMHTs. It used a pragmatic non-randomised two-group pre-post study to evaluate the implementation process in CMHTs. Implementation materials co-produced with service users were provided to the intervention teams for practitioners to use with the support of a senior social worker in each mental health National Health Service Trust ( n = 5). Service users were interviewed at baseline ( n = 151) and at six-month follow-up ( n = 127), and their outcome and cost data were analysed on an intention-to-treat basis. Analysis of primary and secondary outcome variables found no differences between the intervention and control groups. The economic evaluation found no significant differences between groups in mean costs or outcomes. The findings suggest that it could be difficult for social workers to implement Connecting People in CMHTs or that it does not improve outcomes for CMHT users.